2019
DOI: 10.3233/jad-190193
|View full text |Cite
|
Sign up to set email alerts
|

Causative Mutations and Genetic Risk Factors in Sporadic Early Onset Alzheimer’s Disease Before 51 Years

Abstract: Background: Pathogenic variants in the autosomal dominant genes PSEN1, PSEN2, or APP, APOE4 alleles, and rare variants within TREM2, SORL1, and ABCA7 contribute to early-onset Alzheimer's disease (EOAD). However, sporadic EOAD patients have been insufficiently studied to define the probability of being a carrier of one of these variants. Objective: To describe the proportion of each genetic variation among patients with very young-onset sporadic AD. Methods: We first screened PSEN1, PSEN2, and APP in 154 EOAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Specific mutations lead inevitably to familial Alzheimer's disease (FAD; Lacour et al, 2019;Wong et al, 2020), and gene polymorphisms are associated with late-onset Alzheimer's disease (AD; Morelli et al, 1996;Casadei et al, 1999;Dursun et al, 2008;Du et al, 2016;Zuin et al, 2020), the most common form of AD. Some risk factors such as age, education, apolipoprotein ε4 (ApoE-4), hypertension, diabetes, hyperlipidemia, obesity, smoking, and head trauma have been identified, but none is necessary or sufficient to cause AD (Devanand et al, 2013;Guimas Almeida et al, 2018;Takahashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Specific mutations lead inevitably to familial Alzheimer's disease (FAD; Lacour et al, 2019;Wong et al, 2020), and gene polymorphisms are associated with late-onset Alzheimer's disease (AD; Morelli et al, 1996;Casadei et al, 1999;Dursun et al, 2008;Du et al, 2016;Zuin et al, 2020), the most common form of AD. Some risk factors such as age, education, apolipoprotein ε4 (ApoE-4), hypertension, diabetes, hyperlipidemia, obesity, smoking, and head trauma have been identified, but none is necessary or sufficient to cause AD (Devanand et al, 2013;Guimas Almeida et al, 2018;Takahashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There may still be genes that are yet to be discovered or the genetic test used may be insufficient to pick up all types of mutations. Previous publications using NGS techniques show approximately 12%–13% mutation detection rate in dementia patients with a young age of onset with or without a family history, especially in the PSEN1 gene 5,8 . Analysis of WGS data from a clinical cohort of patients with dementia onset ≤65 years (authors' unpublished data), also showed a 14% chance of finding a causative mutation in those with dementia onset under the age of 65 and a further 20% chance of finding a genetic risk factor for their dementia, with most patients having no cause identified.…”
Section: Genetic Counselling In Dementiamentioning
confidence: 82%
“…Even in the absence of a reported family history, a very young age of onset (i.e., younger than 51 years) has been shown to result in approximately 12.3% chance of finding a pathogenic mutation, especially in the PSEN1 gene 8–18 . Whilst not all EOD has a genetic basis and not all people with dementia onset over the age of 65 years are ‘non‐genetic’, the chances of finding a clinically meaningful genetic diagnosis remains higher in EOD (especially when combined with a family history), as well as those with a strong Mendelian type of family history regardless of age of onset.…”
Section: Genetic Dementiasmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 However, an increasing number of pathogenic variants in the 3 genes— APP , 6 PSEN1 7 and PSEN2 8 —causative for familial AD have also been identified in sEOAD. 9 Moreover, rare variants in other genes associated with neurodegenerative diseases, such as PARK2 , FUS , and MAPT , have also been associated with sEOAD. 10 Genetic studies on PCA are relatively few and there are only 4 pathogenic mutations ( PSEN1 G223R, PSEN2 M239I, MAPT V363I, and GRN R110X) that have been reported.…”
mentioning
confidence: 99%